Single-cell synaptome mapping: its technical basis and applications in critical period plasticity research - Uchigashima, Motokazu; Mikuni, Takayasu (Frontiers in Neural Circuits, 2024)
Our brain adapts to the environment by optimizing its function through experience-dependent cortical plasticity. This plasticity is transiently enhanced during a developmental stage, known as the “critical period,” and subsequently maintained at lower levels throughout adulthood. Thus, understanding the mechanism underlying critical period plasticity is crucial for improving brain adaptability across the lifespan. Critical period plasticity relies on activity-dependent circuit remodeling through anatomical and functional changes at individual synapses. However, it remains challenging to identify the molecular signatures of synapses responsible for critical period plasticity and to understand how these plasticity-related synapses are spatiotemporally organized within a neuron. Recent advances in genetic tools and genome editing methodologies have enabled single-cell endogenous protein labeling in the brain, allowing for comprehensive molecular profiling of individual synapses within a neuron, namely “single-cell synaptome mapping.” This promising approach can facilitate insights into the spatiotemporal organization of synapses that are sparse yet functionally important within single neurons. In this review, we introduce the basics of single-cell synaptome mapping and discuss its methodologies and applications to investigate the synaptic and cellular mechanisms underlying circuit remodeling during the critical period.